Incidence of ABO and Rh D blood group among the people attending in Transfusion Medicine Department of Dhaka Medical College Hospital (Journal of Dhaka Medical College, 2013)
DOI: http://dx.doi.org/10.3329/jdmc.v21i1.13236 J. Dhaka Med. Coll. 2012; 21(1): 37-40